Algebra, Codes and Cryptology : First International Conference, A2C 2019 in honor of Prof. Mamadou Sanghare, Dakar, Senegal, December 5-7, 2019 : Proceedings /: First International Conference, A2C 2019 in honor of Prof. Mamadou Sanghare, Dakar, Senegal, December 5-7, 2019 : Proceedings. ([2019]) - Unknown
No abstract available